Pembelajaran Seni Tari Sigeh Pengunten Terhadap Perkembangan Kreativitas dan Kepribadian Siswa - Julionita, Ni Komang; Karja, I Wayan (Jurnal Penelitian Mahasiswa Indonesia, 2024)
This research evaluates the impact of the Sigeh Pengunten dance on the creativity and personality of students at SMP Negeri 1 Seputih Mataram Lampung. The results indicate a significant improvement in the creativity and character of students engaged in learning the Sigeh Pengunten dance. The integration of this dance art into the curriculum brings positive benefits, promoting collaboration, communication, and critical thinking. The research highlights that the Sigeh Pengunten dance not only stimulates students' creativity through free and expressive movements but also shapes positive personalities. The Malay philosophy of Piil Pesengiri, reflected in the dance movements, serves as the foundation for character formation, teaching values of honor and cheerfulness. In the context of learning, the incorporation of the Sigeh Pengunten dance helps students develop communication, emotional, and creative skills. Students not only sharpen their creativity through dance but also build collaboration and communication in the creative process. This process also stimulates critical thinking, enriching students' innovative thinking. The significance of the Sigeh Pengunten dance extends beyond creativity, serving as a means for the development of students' social and emotional skills. The integration of dance art shapes individuals who not only think critically but also possess emotional balance and strong social abilities. Thus, the Sigeh Pengunten dance proves its integral role in creating a holistic and profound learning environment at SMP Negeri 1 Seputih Mataram Lampung.